1999
DOI: 10.1590/s0037-86821999000400013
|View full text |Cite
|
Sign up to set email alerts
|

Observações sobre o diagnóstico laboratorial e a epidemiologia da leishmaniose tegumentar no Estado do Paraná, sul do Brasil

Abstract: Between 1986 and 1997 a total of 1418 patients were examined at the Clinical Analysis Teaching and Research Laboratory of Maringá State University (LEPAC/UEM) for cutaneous leishmaniasis by direct examination of stained smears made from the lesions, the Montenegro skin test and the indirect immunofluorescent antibody test. Nine hundred and fifty five patients (67.3%) were positive for at least one of the three tests and of these 804 (84.2%) were considered to have contracted the disease in Paraná State; 665 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
4
25

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 12 publications
4
42
4
25
Order By: Relevance
“…However, the occurrence of cases in the age ranges of up to 15 and over 65 years, for both sexes, also suggests intra-or peri-domiciliary transmission occurred, corroborating data from the north of Paraná State (Roberto et al, 1997;Lima et al, 2002) and on an endemic area of the State of Minas Gerais, Brazil (Passos et al, 2001). In the present study, IFA showed a higher rate of positivity than the MST or DPS in the diagnosis of ACL, contrasting with results obtained by Silveira et al (1999), who found higher positivity for the MST in patients from the same geographical area. The sensitivity of IFA in the present study was similar to that found in studies on other endemic areas (Marzochi et al, 1980;Lugo de Yarbuh et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, the occurrence of cases in the age ranges of up to 15 and over 65 years, for both sexes, also suggests intra-or peri-domiciliary transmission occurred, corroborating data from the north of Paraná State (Roberto et al, 1997;Lima et al, 2002) and on an endemic area of the State of Minas Gerais, Brazil (Passos et al, 2001). In the present study, IFA showed a higher rate of positivity than the MST or DPS in the diagnosis of ACL, contrasting with results obtained by Silveira et al (1999), who found higher positivity for the MST in patients from the same geographical area. The sensitivity of IFA in the present study was similar to that found in studies on other endemic areas (Marzochi et al, 1980;Lugo de Yarbuh et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the patients studied were from the male working-class population, suggesting an extra-domi- Variables associated with the post-treatment healing of lesions 845 ciliary transmission of ACL, as was previously observed in the north of the state of Paraná (Silveira et al, 1999;Castro et al, 2002). However, the occurrence of cases in the age ranges of up to 15 and over 65 years, for both sexes, also suggests intra-or peri-domiciliary transmission occurred, corroborating data from the north of Paraná State (Roberto et al, 1997;Lima et al, 2002) and on an endemic area of the State of Minas Gerais, Brazil (Passos et al, 2001).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Os testes sorológicos são pouco utilizados para o diagnóstico da LTA 20 , sendo necessária a associação de diferentes métodos para aumentar a positividade do diagnóstico da doença 16 . Têm Têm Têm sido encontradas algumas dificuldades na utilização do teste intradérmico de Montenegro para o diagnóstico da leishmaniose, como por exemplo, o uso de diferentes espécies do parasita e de uso de diferentes espécies do parasita e de diferentes formas de preparação de antígenos além da capacidade do teste em induzir reações de hipersensibilidade tardia quando realizada pela segunda vez.…”
unclassified